Semar: A Personal Model for Counselors - Galang Surya Gumilang; Mona Robinson (Pamomong: Journal of Islamic Educational Counseling, 2022)
Semar is an Indonesian wayang figure, a servant to other wayang characters Pandawa. Semar's personality is shown as a good, wise and wise individual, so he is suitable to be used as a counselor's personality model. This qualitative study applied Gadamerian hermeneutics, an objective type of hermeneutic research. The primary data in this study were texts discussing Semar, namely “Apa dan Siapa Semar” by Sri Mulyono and “Semar Dunia Batin Orang Jawa” by Tuti Sumukti. The data were also collected through an interview with Indonesian wayang expert, Ki Manteb Sudarsono. This study found that Semar’s (1) advisor, (2) congruent, (3) honest, and (4) empathetic personalities could be used as a counselor’s personal model.